2000
DOI: 10.1089/neu.2000.17.333
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury in ICAM-1–Deficient Mice: Assessment of Functional and Histopathological Outcome

Abstract: Adhesion molecule-mediated adhesion and extravasation of leukocytes may constitute a mechanism of secondary tissue damage following spinal cord injury (SCI). The objective of the present study was to determine to what extent genetic deficiency in the adhesion molecule ICAM-1 influences functional and histopathological measures of outcome following SCI. ICAM-1-/- (n = 11) and wild-type (n = 9) mice were subjected to a compression-type SCI. Assessment of hind-limb motor function was done on days 1, 2, 4, 7, 10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…10 We have been using a compression SCI model to study the pathophysiology of primary and secondary injury. [11][12][13][14][15][16] Previously, we have shown that in this model there is a necrotizing lesion at the site of compression after moderate injury, which causes atrophy of the spinal cord at 14 days postinjury. 17 Morphometry of hematoxylin and eosin (H&E) and luxol fast blue (LFB)-stained sections as well as microtubule-associated protein 2 (MAP-2) immunocytochemical staining showed that both gray and white matter were reduced.…”
Section: Introductionmentioning
confidence: 84%
“…10 We have been using a compression SCI model to study the pathophysiology of primary and secondary injury. [11][12][13][14][15][16] Previously, we have shown that in this model there is a necrotizing lesion at the site of compression after moderate injury, which causes atrophy of the spinal cord at 14 days postinjury. 17 Morphometry of hematoxylin and eosin (H&E) and luxol fast blue (LFB)-stained sections as well as microtubule-associated protein 2 (MAP-2) immunocytochemical staining showed that both gray and white matter were reduced.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, antioxidant (antioxidant enzyme)-targeted interventions in conjunction with other therapeutic approaches may effectively reduce the neuronal damage from secondary effects of SCI, particularly those involving motor neuron cell death after SCI. 27 Mouse SCI model Selection of mouse SCI model in the current study was primarily based on the availability of transgenic 28,29 and knockout 30,31 mouse systems as the useful tools to investigate the secondary effects of SCI on neuronal cell vulnerability. The transgenic (knockout) mouse model systems can be potentially applied to define the specific role of specific genetic element in protection/facilitation of neuronal vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…The transgenic (knockout) mouse model systems can be potentially applied to define the specific role of specific genetic element in protection/facilitation of neuronal vulnerability. [28][29][30][31] Several mouse SCI models, such as weight-drop, contusion and compression have been well established and applied to study SCI-mediated neuropathophysiological functions. 1,32 The reason that we adopted the compression approach to induce spinal cord injury is based on its reproducibility and simplicity.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly related to spinal cord compression/transection due to a vertebral bone fracture or distraction/stretching of the spinal column [ 2 , 3 , 4 ]. The secondary mechanisms of SCI are composed of a cascade of temporal events that include neurogenic shock [ 5 , 6 ], hemorrhage and ischemia-reperfusion [ 7 , 8 ], an increase of intracellular calcium and calcium-mediated activation of proteases (e.g., calpain) and lipases [ 9 , 10 , 11 , 12 , 13 ], mitochondrion dysfunction, the generation of free radicals and nitric oxide as well as other oxidants [ 14 ], the release of excitatory neurotransmitters (e.g., glutamate) and excitotoxicity [ 15 , 16 ], which in turn results in the apoptosis of neurons, oligodendrocytes, microglia and astrocytes [ 17 , 18 , 19 ], Wallerian degeneration of injured axons [ 20 ], the infiltration of neutrophils and the migration of macrophages and microglia [ 21 , 22 , 23 , 24 ] as well as astrocyte activation and scar formation [ 25 ]. These secondary pathomechanisms are associated with the majority of the morbidity and mortality after SCI.…”
Section: Spinal Cord Injury (Sci) Epidemiology and Pathophysiologymentioning
confidence: 99%